Menumbuhkan Altruisme Siswa Melalui Kisah Nabi Ayyub a.s dan Khalifah Umar bin Khattab r.a - Ali Audah; Aminto; audah, ali (Prodi PGMI STAI At-Tahdzib Ngoro Jombang, 2023)
Altruistic behavior needs to be cultivated from an early age. Altruism encourages children to help people who are in trouble or in pain. Strong moral emotions encourage children to act rightly, because children are able to see the distress of others, thus preventing them from taking actions that can hurt others. This study aims to foster altuism through the stories of the Prophet Ayyub As and Caliph Umar bin Khattab Ra. This experimental study divided 39 Class VI students of Madrasah Ibtida'iyah Darul Huda Purwoasri Kediri, into three groups, each group consisting of 13 students, namely the experimental group-1 received the story of the Prophet Ayyub As; experimental group-2 got the story of Caliph Umar bin Khattab Ra, and; the control group did not get the story. The data collection tool used is an altuism questionnaire. Actions in the form of stories are given in controlled situations. After finishing the story for 1 week, a post-test of altruism was carried out. Altruism data between groups were analyzed by One-way Anova. The results showed that the stories of the Prophet Ayyub As and the Caliph Umar bin Khattab Ra had a positive effect on fostering student altruism. Spiritual themed stories are useful for developing altruism since early adolescence. Adolescents become like to give or share, like to cooperate, like to do charity, like to help, honest, like to give, consider the rights and welfare of others.